Benzo[a]pyrene modulation of acute immunologic responses in red Sea bream pretreated with lipopolysaccharide. Issue 5 (19th May 2012) - Bo, Jun; Gopalakrishnan, Singaram; Fan, Dan‐Qing; Thilagam, Harikrishnan; Qu, Hai‐Dong; Zhang, Nai; Chen, Fang‐Yi; Wang, Ke‐Jian
<x xml:space="preserve">Abstract</x> The effects of polycyclic aromatic hydrocarbons (PAHs) have been reported to modulate the immune response in aquatic animals, but the collected information of their effects on fish immunity is so far ambiguous. This study demonstrated that Benzo[a]pyrene (BaP) exposure altered the expression pattern of an antimicrobial peptide hepcidin (PM‐hepc) gene and the activities of some immune‐associated parameters in the lipopolysaccharide (LPS)‐challenged red sea bream (Pagrus major). It was observed that LPS could increase respiratory burst, lysozyme and antibacterial activity in P. major. However when the P. major was exposed to different concentrations of BaP (1, 4, or 8 μg L−1) for 14 days and then challenged with LPS there was no significant change in the lysozyme and antibacterial activity. It was further observed that LPS could induce the PM‐hepc mRNA expression at 3, 6, and 12‐h post‐LPS challenge. However, when P. major was exposed first to BaP for 14 days and then challenged with LPS, the expression of PM‐hepc mRNA was delayed in the liver until 24 h and not significantly induced until 48 and 96 h. The mRNA expression pattern was completely different from that only with LPS challenge, showing that BaP exposure changed the PM‐hepc mRNA expression pattern of fish with LPS challenge. This study demonstrated that BaP exposure can weaken or inhibit the induction of lysozyme and antibacterial activity in the LPS‐challenged P. major; conversely BaP exposure could enhance the mRNA expression of PM‐hepc gene, indicating that the effect of BaP has different modulatory mechanism on hepcidin genes and immune‐associated parameters. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 517–525, 2014.